2021
DOI: 10.3389/fagro.2021.661295
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bradyrhizobium spp. Nodulating Lupinus cosentinii and L. luteus Microsymbionts in Morocco

Abstract: In this work, we analyzed the diversity of the nodule-forming bacteria associated with Lupinus luteus and Lupinus cosentinii grown in the Maamora Cork oak forest acidic soils in Morocco. The phenotypic analysis showed the high diversity of the strains nodulating the two lupine's species. The strains were not tolerant to acidity or high alkalinity. They do not tolerate salinity or high temperatures either. The strains isolated from L. luteus were more tolerant to antibiotics and salinity than those isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…These findings supported earlier studies where rhizobia were isolated from woody legumes in general and Dryland acacia tree species in particular were able to tolerate higher salinity [24][25] . The range of salinity tolerance in rhizobia can vary significantly between species, and even within strains of the same species 26 . While Assefa (1993) 27 discovered that some strains of slow-growing rhizobia from woody legumes were more tolerant to NaCl than fast-growing species, Zerhari et al 28 reported that fast-growing rhizobia isolated from some Acacia species were tolerant to high NaCl concentrations compared to slow-growing strains.…”
Section: Discussionmentioning
confidence: 99%
“…These findings supported earlier studies where rhizobia were isolated from woody legumes in general and Dryland acacia tree species in particular were able to tolerate higher salinity [24][25] . The range of salinity tolerance in rhizobia can vary significantly between species, and even within strains of the same species 26 . While Assefa (1993) 27 discovered that some strains of slow-growing rhizobia from woody legumes were more tolerant to NaCl than fast-growing species, Zerhari et al 28 reported that fast-growing rhizobia isolated from some Acacia species were tolerant to high NaCl concentrations compared to slow-growing strains.…”
Section: Discussionmentioning
confidence: 99%
“…microsymbionts and their closest relatives. Recently, two new putative Bradyrhizobium genospecies within the genistearum symbiovar were identified [ 79 , 80 ]. As could be expected, all lupin-nodulating species in the genus Bradyrhizobium are phylogenetically close, according to a 16S rRNA gene sequence-derived tree ( Figure 1 ).…”
Section: Rhizobia That Nodulate Lupins Many More Than Initially Expectedmentioning
confidence: 99%